Age and Parity Relationship with Premature Delivery - Puteri, Sri Kurnia Sah; Sumarmi; Nuryana, Riska; Mantasia; Al Ayum, Maulia (Omni Nursing Journal, 2025)
Background: Premature delivery is defined as the delivery process experienced at a gestational age of less than 37 weeks or a fetus that weighs less than 2,500 grams. Preterm birth not only results in perinatal death, but it also often causes short-term and long-term disability in the affected infants. Objective: To analyze the relationship between age and parity to premature delivery. Methods: This study is a type of analytical research using cross-sectional data with secondary data. Results: There was an age relationship with premature delivery with a value of p = 0.000 < 0.05 and a parity relationship with premature delivery at Prof. Dr. H m. Anwar Makkatutu Hospital, Bantaeng Regency with a p value = 0.000 < 0.05. Conclusion: Good nutritional status plays a very important role in supporting academic achievement, both through its influence on brain development, energy, cognitive function, and children's learning motivation.